PENGARUH BUKU SAKU DIGITAL PADA KULIAH HUKUM PERDATA TERHADAP PENINGKATAN KEMANDIRIAN BELAJAR MAHASISWA - Sri Hadiningrum; Dewi Pika Lbn Batu; Syuratty Astuti R Manalu; Maryatun Kabatiah (Akademika, 2023)
The aim of this study is to analyze how using a digital pocketbook can enhance students' learning independence in civil law classes. Understanding the laws controlling the legal relationships between people/individuals and legal entities is possible through civil law courses offered by the Pancasila and Civic Education Departments. This study employed a descriptive quantitative methodology. Fifth-semester Universitas Negeri Medan civic education students served as the research subjects. Observation, interviews, and documentation were used to gather the data; data reduction involved choosing, focusing on, and simplifying the data; data display involved presenting the data in a table and figure; and conclusion involved providing meaning, confirming, and verifying the data. The outcomes demonstrated that utilizing the digital pocketbook effectively increased student learning independence. The average student questionnaire response rate for Digital Pocketbook in civil law courses is 84.58%. Thus, it could be concluded that learning independence is impacted by digital pocketbooks, using digital pocketbooks in civil law classes can help students become more independent learners.